Tick-borne zoonoses in the Order Rickettsiales and Legionellales in Iran: A systematic review. - Faham Khamesipour; Gabriel O Dida; Douglas N Anyona; S Mostafa Razavi; Ehsan Rakhshandehroo (Public Library of Science (PLoS), 2018)
BACKGROUND:Tick-borne zoonoses in the Order Rickettsiales and Legionellales cause infections that often manifest as undifferentiated fevers that are not easy to distinguish from other causes of acute febrile illnesses clinically. This is partly attributed to difficulty in laboratory confirmation since convalescent sera, specific diagnostic reagents, and the required expertise may not be readily available. As a result, a number of tick-borne zoonoses are underappreciated resulting in unnecessary morbidity, mortality and huge economic loses. In Iran, a significant proportion of human infectious diseases are tick-borne, with anecdotal evidence suggesting that tick-borne zoonoses are widespread but underreported in the country. Epidemiological review is therefore necessary to aid in the effective control and prevention of tick-borne zonooses in Iran. The aim of this review is to provide an in-depth and comprehensive overview of anaplasmosis, ehrlichiosis, spotted fever group rickettsioses and coxiellosis in Iran. METHODS:Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, all relevant publications on tick-borne zoonoses in the Order Rickettsiales and Legionellales in Iran were searched using a number of search terms. The search was confined to authentic resources from repositories of popular data bases among them PubMed, Web of Science, Google Scholar, Science Direct, SpringerLink and SCOPUS. The search items included peer reviewed journals, books and book chapters published between 1996 and 2017. RESULTS:A total of 1 205 scientific publications and reports were sourced, of which 63 met the search criteria and were reviewed. Of the 63 articles reviewed, 36 (57.1%) reported on coxiellosis, 15 (23.8%) on anaplasmosis, 11 (17.5%) on ehrlichiosis and 1(1.6%) on spotted fever group rickettsiae in a large scale study involving four countries, among them Iran. The existence of tick-borne pathogens in the Order Rickettsiales and Legionellales was confirmed by molecular, serological and microscopic techniques conducted on samples obtained from sheep, cattle, goats, camels, poultry, animal products (milk and eggs), dogs, ticks and even human subjects in different parts of the country; pointing to a countrywide distribution. DISCUSSION:Based on the review, coxiellosis, anaplasmosis, ehrlichiosis, and SFG rickettsiae can be categorized as emerging tick-borne zoonotic diseases in Iran given the presence of their causiative agents (C. burnetii, A. phagocytophilum, A. marginale, A. bovis, A. ovis, A. central, E. canis, E. ewingii, E. chaffeensis and R. conorii) collectively reported in a variety of domestic animals, animal products, arthropods and human beings drawn from 22 provinces in Iran. CONCLUSION:Given the asymptomatic nature of some of these zoonoses, there is a high likelihood of silent transmission to humans in many parts of the country, which should be considered a public health concern. Presently, information on the transmission intensity of tick-borne zoonoses caused by pathogens in the Order Rickettsiales and Legionellales to humans and its public health impact in Iran is scanty.